2022
DOI: 10.3390/cells11243952
|View full text |Cite
|
Sign up to set email alerts
|

miR-301a Deficiency Attenuates the Macrophage Migration and Phagocytosis through YY1/CXCR4 Pathway

Abstract: (1) Background: the miR-301a is well known involving the proliferation and migration of tumor cells. However, the role of miR-301a in the migration and phagocytosis of macrophages is still unclear. (2) Methods: sciatic nerve injury, liver injury models, as well as primary macrophage cultures were prepared from the miR-301a knockout (KO) and wild type (WT) mice to assess the macrophage’s migration and phagocytosis capabilities. Targetscan database analysis, Western blotting, siRNA transfection, and CXCR4 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…When damage occurs in the body, cells migrate quickly to repair the damage [76]. The results of Xu et al found that miR-301a knockout mice had reduced macrophage migration capacity, which affected subsequent damage repair in damaged tissues [77]. Liu et al discovered that miR-874-3p upregulation diminishes the migration capability of osteosarcoma cells [78].…”
Section: Discussionmentioning
confidence: 99%
“…When damage occurs in the body, cells migrate quickly to repair the damage [76]. The results of Xu et al found that miR-301a knockout mice had reduced macrophage migration capacity, which affected subsequent damage repair in damaged tissues [77]. Liu et al discovered that miR-874-3p upregulation diminishes the migration capability of osteosarcoma cells [78].…”
Section: Discussionmentioning
confidence: 99%
“…Indicated that it may be a competitive relationship between YY1 and COX-2 promoter, p300 and HDAC1/2 after lipopolysaccharide treatment (88). In addition, Xu et al indicates that miR-301a/YY1/CXCR4 signaling pathway plays an important role in macrophage migration and phagocytosis (87). Hence, these results strongly suggest that YY1 is critically important for the tumor immune microenvironment.…”
Section: Other Immune-related Cellsmentioning
confidence: 93%
“…In addition, Xu et al. indicates that miR-301a/YY1/CXCR4 signaling pathway plays an important role in macrophage migration and phagocytosis ( 87 ). Hence, these results strongly suggest that YY1 is critically important for the tumor immune microenvironment.…”
Section: Role Of Yy1 In the Tumor Microenvironmentmentioning
confidence: 99%
“…Additionally, miRNAs exert a considerable influence on the migration and phagocytic functions of macrophages. As an illustration, the deletion of miR-301a diminishes macrophage migration and phagocytosis through the YY1/CXCR4 signaling pathway ( 61 ). Despite the abundance of research, the complex interactions between miRNAs and macrophages demand further comprehensive exploration.…”
Section: Macrophagementioning
confidence: 99%